WRINKLED1, a "master regulator" in transcriptional control of plant oil biosynthesis - Kong, Que (2020)
A majority of plant species generate and accumulate triacylglycerol (TAG) in their seeds, which is the main resource of carbon and energy supporting the process of seedling development. Plant seed oils have broad ranges of uses, being not only important for human diets but also renewable feedstock of industrial applications. The WRINKLED1 (WRI1) transcription factor is vital for the transcriptional control of plant oil biosynthetic pathways. Since the identification of the Arabidopsis WRI1 gene (AtWRI1) fifteen years ago, tremendous progress has been made in understanding the functions of WRI1 at multiple levels, ranging from the identification of AtWRI1 target genes to location of the AtWRI1 binding motif, and from discovery of intrinsic structural disorder in WRI1 to fine-tuning of WRI1 modulation by post-translational modifications and protein-protein interactions. The expanding knowledge on the functional understanding of the WRI1 regulatory mechanism not only provides a clearer picture of transcriptional regulation of plant oil biosynthetic pathway, but also helps generate new strategies to better utilize WRI1 for developing novel oil crops.